Analysis of Production Process Time Based on The Level of Hardness in The Production Material - yahya alhafiizh arifin (METALOGRAM, 2025)
Analyzing production process time is a key strategy to enhance efficiency and productivity in manufacturing. This study investigates the relationship between material hardness and processing time across stages like cutting, forming, and finishing. Various materials, including low-carbon steel, high-carbon steel, and alloys, were tested under identical operational conditions. Material hardness was measured using Rockwell and Brinell tests, while production time was recorded for each stage. Results show that higher material hardness leads to longer process times, especially during cutting and forming, due to increased resistance and tool friction. Softer materials, though faster to process, are more prone to deformation. These findings offer valuable insights for manufacturers in selecting materials that balance mechanical properties and efficiency, helping reduce production time, boost productivity, and lower costs without compromising product quality.